Peran Teknik Handheld dalam Transformasi Emosi Tokoh Codename 13 pada Film The Shadow Strays - Delva Luthfiati; Dynia Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the use of handheld camera techniques in portraying the emotional transformation of Codename 13 in The Shadow Strays. The film presents the protagonist’s emotional development through a series of psychological changes that evolve alongside the narrative conflict, making it a compelling subject for cinematographic analysis. This research employs a qualitative descriptive method with data collected through observation, documentation, literature review, and interviews with the film’s Director of Photography (DOP), Batara Goempar. The analysis is based on Robert Plutchik’s Wheel of Emotions theory and cinematography theory to examine the relationship between handheld camera movements and the character’s emotional transformation. The findings reveal that the handheld technique functions not only as a camera operation method but also as a visual language capable of representing Codename 13’s emotional progression throughout the film. Variations in camera stability, movement rhythm, direction, and framing are utilized to reinforce emotions such as anticipation, joy, anger, sadness, fear, and surprise experienced by the character. The study further indicates that changes in handheld camera characteristics are closely related to the intensity of the emotions being portrayed, where higher emotional pressure is represented through increasingly dynamic and unstable camera movements. Therefore, the handheld technique in The Shadow Strays serves as an effective cinematographic element for communicating the character’s emotional dynamics and strengthening narrative meaning through visual storytelling.